Venom Ophthalmia and Ocular Complications Caused by Snake Venom - Chang, Kun-Che; Huang, Yu-Kai; Chen, Yen-Wen; Chen, Min-Hui; Tu, Anthony T.; Chen, Yen-Chia (Toxins, 2020)
Little is known about the detailed clinical description, pathophysiology, and efficacy of treatments for ocular envenoming (venom ophthalmia) caused by venom of the spitting elapid and other snakes, as well as ocular complications caused by snake venom injection. In this paper, we review clinical information of case reports regarding venom ophthalmia and snake venom injection with associated ocular injuries in Asia, Africa, and the United States. We also review the literature of snake venom such as their compositions, properties, and toxic effects. Based on the available clinical information and animal studies, we further discuss possible mechanisms of venom ophthalmia derived from two different routes (Duvernoy’s gland in the mouth and nuchal gland in the dorsal neck) and the pathophysiology of snake venom injection induced ocular complications, including corneal edema, corneal erosion, cataract, ocular inflammation, retinal hemorrhage, acute angle closure glaucoma, as well as ptosis, diplopia, and photophobia. Finally, we discuss the appropriate first aid and novel strategies for treating venom ophthalmia and snake envenoming.